Analisis Dampak Kinerja Ekspor Kabupaten Banyuwangi Terhadap Perekonomian Indonesia Berdasarkan Sektor Lapangan Usaha Tahun 2023 Melalui Pendekatan LQ (Location Quotient) - Kharisma Bintang M.T.; Eksel Perdian Anggara; Dwi Arief Rahman; Rendra Kurniawan; Ignatius Edward Revalyno V.O; Arga Christian Sitohang (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the economic structure and the level of industrialization in Banyuwangi Regency in 2023 using the Location Quotient (LQ) approach. The data used were obtained from the Central Bureau of Statistics (BPS), specifically the Gross Regional Domestic Product (GRDP) at current prices by industrial sector for both Banyuwangi Regency and East Java Province in 2023. The analysis shows that the manufacturing sector has an LQ value of 0.41, indicating that it is not a base sector in the region. In contrast, the base sectors include agriculture, forestry, and fisheries (LQ = 2.34), mining and quarrying (LQ = 1.85), construction (LQ = 1.55), and education services (LQ = 1.18). These findings indicate that Banyuwangi's economy still relies heavily on primary sectors and has not yet undergone a significant structural transformation toward a more industrial-based economy. Therefore, strategic efforts are needed to develop local industries based on regional resources and to enhance value-added production in order to promote more sustainable and inclusive industrialization.